Development of an Accrual-Based Cash Accounting Information System - Ahmad Ashifuddin Aqham; Indra Ava Dianta; Eko Siswanto (Jurnal Ilmiah Sistem Informasi, 2026)
The management of financial transactions is essential for ensuring effective and reliable financial administration. PT Mitra Mandiri Transindo Semarang previously relied on manual procedures for recording cash receipts and disbursements, resulting in reporting delays, data redundancy, difficulties in retrieving historical records, and a higher risk of human error. This study aims to develop a web-based accrual accounting information system that integrates account management, cash receipts, cash disbursements, and financial reporting. The study employed a Research and Development (R&D) approach involving problem identification, data collection, system analysis and design, validation, implementation, revision, and testing. Data were collected through observation, interviews, and literature review. The system was developed using PHP and MySQL and evaluated through Black Box Testing. The results showed that all major system functions operated successfully according to user requirements. The developed system improved transaction recording efficiency accelerated financial report preparation, reduced recording errors, facilitated data retrieval, and supported more accurate financial information through accrual-based recognition. Therefore, the system provides an effective solution for improving financial administration and supporting managerial decision-making.